Prospek Pengelolaan Sumber Daya Perikanan Berbasis Ekosistem: Studi Empiris Di Karimunjawa* - Indah Susilowati (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2013)
The objectives of the study are: to compare the model of fisheries management with conventional versus new paradigm; to explore the prospect of new fisheries management model; to formulate the initial strategy of fisheries management model using EBFM. The ecosystem of Karimunjawa is selected as the pilot project of this research. The competent 25 keypersons were selected using purposive quoted sampling for interview. Descriptive statistics, meta-analysis and AHP were employed to analize the data. The results showed that the conventional fisheries management models were rather ineffective to answer the current situation of fisheries resource. We need facing out to find a suitable approach of fisheries management model. One of the proposed new paradigm is EBFM. This model indicates has a good prospect to manage the fisheries resource in the study area. This study suggests that EBFM model should be under-tried out. If it is acceptable, then the model can be implemented for other region.